96-well plate-based aggregometry. (3rd October 2018) - Chan, Melissa V.; Armstrong, Paul C.; Warner, Timothy D.
Abstract: While there are many bench and bedside tests to assess platelet reactivity, ex vivo light transmission aggregometry (LTA) remains the gold standard. LTA, however, is expensive, time-consuming and requires dedicated equipment and staff, making it impractical in many situations. In addition, there is significant variability between data generated at different testing sites meaning that tests often need to be repeated if a patient is transferred to the care of a different hospital. As such, there is clearly an unmet need for standardization of platelet testing. Using the principles of LTA, aggregometry can be conducted in 96-well plates with readings being made in a standard plate reader. This approach allows for the assessment of multiple concentrations of agonists, since the volume of platelets required for each test is significantly lower than for LTA. Furthermore, the lyophilization of a set panel of agonists to a 96-well plate to produce a stable assay substrate allows the production of portable, standardized plates that can be used to generate reproducible tests at multiple sites. In this review, we will discuss the methods and uses of 96-well plate aggregometry for both research and the clinic.